Pacific Youth Local and Global Futures - Lee, Helen (ANU Press, 2019)
Pacific populations are becoming younger and this 'youth bulge' is often perceived as a dangerous precursor to civil unrest. Yet young people are also a valuable resource holding exciting potential for the future of island nations. Addressing these conflicting views of youth, this volume presents ethnographic case studies of young people from across the Pacific and the diaspora. Moving beyond the typical focus on 'youth problems' in reports by Pacific governments and development agencies, the authors examine the highly diverse lives and perspectives of young people in urban and rural locations. They celebrate the contributions of youth to their communities while examining the challenges they face. The case studies explore the impacts of profound local and global changes and cover a wide sweep of youth experiences across themes of education, employment and economic inequalities, political and civil engagement, and migration and the diaspora. Contributors to this volume bring many decades of experience of research with Pacific people as well as fresh perspectives from early career and graduate researchers. Most are anthropologists and their chapters contribute to the interdisciplinary fields of youth studies and Pacific studies, offering thought-provoking insights into the possibilities for Pacific youth as they face uncertain futures.